The role of benefits in sustaining HRM outcomes : an empirical research study - Galetić, Lovorka (Array, 2020)
Benefits are a type of indirect compensation that aims to achieve many goals. Primarily, however, companies provide benefits to prove that they care for their employees’ personal needs, or because they wish to offer an attractive and competitive total compensation package. Since benefits account for a growing portion of the total compensation package costs, and taking into account that the motivating potential of benefits has lately been brought into question, we aim to analyze the role of benefits in achieving primary goals of human resource management, i.e., attracting, retaining and engaging employees in Croatian companies. Therefore, an empirical study was conducted on a sample of Croatian companies, which shows security, pension and health benefits, which are usually highly valued by employees, are under-represented in Croatian companies. In the case of administrative and manual employees, social activities, non-mandatory health and pension insurance and work from home were positively related to retention. However, statistically significant relationships between benefits mostly related to work-life balance and HR-related outcomes were almost exclusively negative in the case of experts, while only non-mandatory health insurance was found to be potentially useful in engaging and retaining experts. Therefore, employers should redesign benefits strategy and consider offering a flexible benefits system as an option.